О словотворчестве российских и польских интернет-пользователей в эпоху глобальной интернационализации - Koriakowcewa, Elena (Studia Rossica Posnaniensia, 2020)
The article deals with the evolution of word-formative types of nouns with new international formants -инг/-ing, -(о)голик/-(о)holik, -завр/-zaur, -оид/-oid that can express the complex concepts of attributive and contextual content. The composition of a new type of words with morphemes -инг/-ing, -(о)голик/-(о)holik, -завр/-zaur corresponds to a historical drift in the formation of analytic and agglutinative lines in the Russian and Polish languages.